Optimization of Culture Conditions for the Production of Extracellular Cellulase from Enterococcus pseudoavium - Meenakshi and P. Palani*, M. Sakthivel, N. Karthikeyan, J. (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Bacteria that inhabit decaying vegetables were isolated and screened for the production of the enzyme, amylase. One species identified as Enterococcus pseudoavium exhibited relatively higher amylase activity of the bacterial species tested. The bacterium produced the highest extracellular amylase at 72 h in a medium containing starch (1% w/v), galactose (0.5% w/v), and peptone (0.5% w/v), at pH 7.0. The extracellular enzyme was partially purified and its starch hydrolyzing potential was evaluated. The organism when grown with paper pulp deinked the pulp completely just after four days of growth. The bacterial cells immobilized in sodium alginate beads when cultured with paper pulp could decolorize it within 4 days. The extracellular amylase produced by Enterococcus pseudoavium effectively deinked and decolorized paper pulp within 4 days after incubation. The enzyme efficiently removed the starch present in fabric and thus it could be very well used as an ingredient in commercial detergent.